Fixed-time control of voltage dynamics of three-phase voltage source inverters with LC output filter - Mohamed Ghazzali; Mohamed Haloua; Fouad Giri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper puts forward a fixed-time cascade voltage control system for threephase voltage source inverters (VSIs) with LC output filter.First, a feedforward decoupling mechanism is used to elminate the dependency between the d-q parts of the control system. Then, proportional-integral (PI) regulators are used for current control in the inner loop. The current reference is provided by a novel VSI control technique developed for fixed-time voltage regulation and reference tracking. The approach suggested in this work tracks and maintains the voltage magnitude at its normalized value in a finite-time and before a maximum settling-time fixed in advance and independent of the system’s initial state. The voltage controller also maintains current stability by providing a smoother and smaller current reference. A comparative study with VSI conventional PI control for linear, nonlinear and unbalanced loads confirms the theoretical results.